2014
DOI: 10.1063/1.4867285
|View full text |Cite
|
Sign up to set email alerts
|

Curvature dependence of the interfacial heat and mass transfer coefficients

Abstract: Nucleation is often accompanied by heat transfer between the surroundings and a nucleus of a new phase. The interface between two phases gives an additional resistance to this transfer. For small nuclei the interfacial curvature is high, which affects not only equilibrium quantities such as surface tension, but also the transport properties. In particular, high curvature affects the interfacial resistance to heat and mass transfer. We develop a framework for determining the curvature dependence of the interfac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…They showed that there was little difference between the interface resistances with three choices of the dividing interface. 31 Resistances both for one-and two-component systems vary continuously with the interface curvature, from negative (bubbles) to zero (planar interfaces) to positive (droplet) values. For one component, also the first derivatives of the interface resistances are continuous.…”
Section: Interface Resistancesmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that there was little difference between the interface resistances with three choices of the dividing interface. 31 Resistances both for one-and two-component systems vary continuously with the interface curvature, from negative (bubbles) to zero (planar interfaces) to positive (droplet) values. For one component, also the first derivatives of the interface resistances are continuous.…”
Section: Interface Resistancesmentioning
confidence: 99%
“…Square gradient theory complements NEMD, Monte Carlo simulations and experiments, in that a comparison with these more sophisticated and time demanding approaches provides insight into the structure of the interface at the mesoscopic level. 26 We shall use equilibrium profiles combined with the integral relations to obtain interface resistances, [29][30][31] and compare these to results from the non-equilibrium square gradient model, with actual gradients in temperature, composition and pressure. 26,32 We present interface resistances which vary continuously with the interface curvature, from negative (bubbles) to zero (planar interface) to positive (droplet) values.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in fundamental thermodynamics of nuclei growth, the high interfacial curvature affects not only equilibrium quantities such as surface tension but also heat and mass transports. [1][2][3] Considering micrometric bubbles, the resonant properties (resonant frequency and Q factor) depend on their size, on the physical characteristics of host medium and on the nature of the enclosed gas. For a given size, the measurement of the resonance makes it possible to estimate physical properties of the host medium or of the gas.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%